Comparison of Early (2 Days) and Later (28 Days) Response of Adipose Tissue to Very Low-Calorie Diet in Obese Women - Šrámková, Veronika; Rossmeislová, Lenka; Krauzová, Eva; Kračmerová, Jana; Koc, Michal; Langin, Dominique; Štich, Vladimír; Šiklová, Michaela (The Journal of clinical endocrinology and metabolism, 2016)
CONTEXT: Beneficial metabolic effects of calorie restriction found in the early stage of hypocalorie diets may be caused by the modulation of metabolic and endocrine function of adipose tissue. OBJECTIVE: The objective of the study was to compare metabolic and inflammation-related characteristics of sc adipose tissue (SAAT) in the early (2 d) and later (28 d) phase of a very low calorie diet (VLCD). Design, Setting, Intervention, and Patients: Seventeen moderately obese premenopausal women followed an 800 kcal/d VLCD for 28 days. Anthropometric measurements, blood sampling, and a biopsy of SAAT were performed before the diet and after 2 and 28 days of the VLCD. MAIN OUTCOME MEASURE(S): mRNA expression of 50 genes related to lipid metabolism, inflammation, and fibrosis were analyzed in SAAT. Secretion of adipokines was determined in SAAT explants and adipokines, fibroblast growth factor 21 (FGF21) and C-reactive protein were measured in plasma. RESULTS: In the early phase of the VLCD, the expression of lipolytic genes was increased, whereas the expression of lipogenic genes was significantly suppressed. The inflammatory markers in SAAT remained unchanged. At the later phase, expression of genes involved in lipogenesis and β-oxidation was markedly suppressed, whereas the expression of inflammatory markers was increased. The changes of lipogenic genes after 28 days of the VLCD correlated with FGF21 changes. CONCLUSION: The early and later phases of a VLCD differ with respect to metabolic and inflammatory responses in SAAT. The expression changes in SAAT in the early phase of the VLCD could not explain the effect of short calorie restriction on the improvement of insulin sensitivity. An interplay of SAAT with liver function during VLCD mediated by FGF21 might be suggested.
Keywords: obezita; exprese genu; Humans; kalorická restrikce; Gene Expression; Caloric Restriction; hodnocení výsledků zdravotní péče; Female; dospělí; lipogeneze; Inflammation; lidé; Lipogenesis; zánět; časové faktory; Adult; Subcutaneous Fat; ženské pohlaví; Obesity; Time Factors; Outcome Assessment, Health Care; Adipokines; adipokiny; podkožní tuk